Comparison between tramadol hydrochloride & nalbuphine hydrochloride in the treatment of per-operative shivering after spinal anaesthesia. - Haque, MF; Rashid, MH; Rahaman, MS; Islam, MR (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Apr;20(2): 201-205 The abstract of this article is available on the PubMed website